HACScale : hardware-aware compound scaling for resource-efficient DNNs - Kong, Hao (2022)
Model scaling is an effective way to improve the accuracy of deep neural networks (DNNs) by increasing the model capacity. However, existing approaches seldom consider the underlying hardware, causing inefficient utilization of hardware resources and consequently high inference latency. In this paper, we propose HACScale, a hardware-aware model scaling strategy to fully exploit hardware resources for higher accuracy. In HACScale, different dimensions of DNNs are jointly scaled with consideration of their contributions to hardware utilization and accuracy. To improve the efficiency of width scaling, we introduce importance-aware width scaling in HACScale, which computes the importance of each layer to the accuracy and scales each layer accordingly to optimize the trade-off between accuracy and model parameters. Experiments show that HACScale improves the hardware utilization by 1.92× on ImageNet, as a result, it achieves 2.41% accuracy improvement with a negligible latency increase of 0.6%. On CIFAR-10, HACScale improves the accuracy by 2.23% with only 6.5% latency growth.